Dynamic query optimisation: towards decentralised methods. (17th December 2009) - Morvan, Franck; Hameurlain, Abdelkader
The execution plans generated by relational query optimisers can be suboptimal because of the inaccuracies of estimations, the unavailability of resources and the instability of the execution environment. To detect and correct this suboptimality, several dynamic optimisation methods were proposed. In this paper, we present a synthesis of the main dynamic optimisation methods. First, we present a set of parameters allowing to characterise and compare dynamic optimisation methods. The comparison reveals that a method must be decentralised in a large-scale distributed environment. Finally, before concluding, we discuss the advantages and drawbacks of proposed decentralised methods.